2021
DOI: 10.1097/gox.0000000000003582
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in the Treatment of Vasopressor-associated Symmetric Peripheral Gangrene

Abstract: Summary: Symmetric peripheral gangrene (SPG) affects peripheral tissues of critically ill patients and can have severe disfiguring and debilitating effects. It can occur in the setting of multiple conditions, and it is associated with the use of vasopressors. There are no evidence-based treatments available for patients who develop SPG. Botulinum toxin has emerged as a potential therapy in vasospastic disorders, and we hypothesized that it may be used in the treatment of tissue ischemia in criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a guinea pig vascular model, it has been previously reported that BoTA attenuates the release of norepinephrine via SNAP-25 cleavage inducing vasodilatation 41 . In addition, BoTA induces the release of VEGF and can also increase nitric oxide synthase expression in skin flaps 13 , 42 .…”
Section: Discussionmentioning
confidence: 96%
“…In a guinea pig vascular model, it has been previously reported that BoTA attenuates the release of norepinephrine via SNAP-25 cleavage inducing vasodilatation 41 . In addition, BoTA induces the release of VEGF and can also increase nitric oxide synthase expression in skin flaps 13 , 42 .…”
Section: Discussionmentioning
confidence: 96%
“…Supporting the role of botulinum toxin in treating pressor induced ischemia, Stoehr et al in 2021 demonstrated similar therapeutics effects after injecting 50 units into the nose of a patient with pressor-induced nasal tip ischemia. 14 To date, there have been no controlled clinical trials looking at the effects of botulinum toxin A on pressor-induced ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…A case reported in 2018 showed successful improvement of the lesion using prostaglandins and low-molecular-weight heparin [ 14 ]. In addition, innovative methods such as botulinum toxin injections offer promise in managing SPG by promoting vasodilation and alleviating cutaneous ischemia ​[ 29 ].…”
Section: Reviewmentioning
confidence: 99%